Locking phenomena in finite element analysis of deep beam and removal method - Hoa, Nguyen Thang; Thinh, Tran Ich (Vietnam Journal of Mechanics, 2005)
Since earlier 30 years ago, Finite Element Methods (FEM) has become an indispensable tool of engineers for analysis mechanical behaviour of structures. Generally displacement models are used in most usual problems. Under certain material conditions, such elements may provide inaccurate results and exhibit slow convergence. Locking phenomena are the cause of these problems and this situation could limit the computation of many kinds of structures. This paper presents a deep beam element based upon mixed formulation, which may illuminate these locking phenomena.